Considerations in Neuromuscular Blockade in the ICU: A Case Report and Review of the Literature - Jessica D. Workum; Stephanie H.V. Janssen; Hugo R.W. Touw (Case Reports in Critical Care)
Neuromuscular blocking agents are regularly used in the intensive care unit (ICU) to facilitate mechanical ventilation in patients with acute respiratory distress syndrome and patient-ventilator dyssynchronies. However, prolonged neuromuscular blockade is associated with adverse effects like ICU-acquired weakness. Residual neuromuscular blockade is, however, not routinely monitored in the intensive care unit, and as such, this phenomenon might be unrecognized and underreported. We report a case in which an unusual prolonged effect of neuromuscular blockade was seen after cessation of the drug, which illustrates the complexity of neuromuscular blockade in the ICU. We advocate for the use of train-of-four measurements in the ICU, recommend to choose cisatracurium over rocuronium in critically ill patients due to their pharmacokinetics when continuous neuromuscular blockade is considered, and propose a subsequent strategy once the choice has been made to start neuromuscular blockade.